RANCANGANSISTEM INFORMASI E-PROCUREMENT BERORIENTASI OBJECT ( STUDI KASUS : PT. KRAKATAU TIRTA INDUSTRI ) - Roy Amrullah; Anita Megayanti (Jurnal Ilmiah Sains dan Teknologi, 2018)
ABSTRAK E-Procurement System PT. Krakatau Tirta Industri hereinafter abbreviated as e-Procurement is the process of procuring goods and / or services within the PT. Krakatau Tirta Industri is electronically web / internet based and is done online. The e-Procurement aims to improve, transparency, process speed, time and cost efficiency, accountability, facilitate control and supervision. The software used for analysis and design is the UML Star. The method used is an object-oriented approach using UML (unified modeling language) namely use case diagrams, sequence diagrams and activity diagrams.